Comparing sub-national policy workers in Canada and the Czech Republic: Who are they, what they do, and why it matters?. Issue 2 (1st June 2014) - Veselý, Arnošt; Wellstead, Adam; Evans, Bryan
Abstract: This article compares profiles and policy-related activities of policy workers (PWs) in thirteen Canadian provinces and territories with PWs in the Czech Republic regions. Canadian data come from 13 separate surveys conducted in provinces and territories in late 2008 and early 2009 ( N = 1357). The Czech data are from analogical large-scale survey carried out at the end of 2012 ( N = 783). First, the paper compares basic characteristics of Canadian and Czech PWs. In the two countries the proportion of men and women is similar and PWs are equally highly educated. Examining other characteristics, however, reveals substantial differences. When compared with the Czech PWs, Canadian PWs tend to be older, more often having social science educational backgrounds, more frequently recruited from academia, stay in a single organization for a shorter period of time and anticipate staying in their current position for only a short time. Second, a comparison of policy-related work activities discerns three basic clusters of policy tasks: policy analysis work, evidence-based work, and consulting/briefing. Canadian PWs are much more involved in evidence-based work, especially in evaluation and policy research. They also deal more with policy analysis activities such as identification of policy issues and options. In contrast, Czech PWs are more engaged in consulting with the public and briefing managers and decision-makers. The article concludes with implications for further research and theory building.